Two new species of Veraphis Casey (Coleoptera, Staphylinidae, Scydmaeninae) from China - Jałoszyński, Paweł (Zootaxa, 2012)
Two new species of the Holoarctic genus Veraphis Casey are described from the sub-Himalayan part of China: V. qinghaiensissp. n. (from Qinghai) and V. calcarifer sp. n. (from Sichuan and Qinghai). Diagnostic characters of the new taxa are illustrated,including the aedeagi and modified fore legs, and possible relationships with previously known Eastern Palaearctic species are discussed.